ANALISIS RISIKO OPERASIONAL ALAT RUBBER TYRED GANTRY (RTG) BATERAI DENGAN METODE FMEA - M. Ray Albani Subait Hayato; Irma Rustini Aju; Fitri Hardiyanti (Proceeding Maritime Business Management Conference, 2024)
The company providing loading and unloading services in Surabaya is a company that handles the loading and unloading of special domestic containers and the process is carried out at the terminal as an operational dock. With the current conditions, one of the port equipment facilities located at the Container Yard (CY) terminal and actively functioning is the Rubber Tyred Gantry (RTG) which consists of 9 tools, 2 of which are Battery RTGs, especially the TTB 13 Battery RTGs which were only used last month. April 2023. However, when this tool was used, potential risks were found in the tool performance data and the failure to achieve production performance in terminal operations in the period April-December 2023. So this research analyzes these risks using the Failure Mode and Effect Analysis (FMEA) method in determining priorities risk and then determine proposed risk management strategies. The results of the research are based on the risk indicator with the highest RPN value, namely the spreader is easier to shake, has a value of 153.56 and risk management strategies is the proposed Human Resources management strategy must adapt more quickly to new tools through training and familiarization programs. So, the TTB 13 Battery RTG tool can work optimally and achieve the targets set by the company.